Validating incentive salience with functional magnetic resonance imaging: association between mesolimbic cue reactivity and attentional bias in alcohol-dependent patients - Vollstädt-Klein, Sabine; Steins-Löber, Sabine; Richter, Anne; Kirsch, Martina; Bach, Patrick; Goltz, Christoph von der; Hermann, Derik; Mann, Karl; Kiefer, Falk (Addiction biology, 2012)
Alcohol-associated cues are able to elicit brain activations in mesocorticolimbic networks that are related to the rewarding properties of the drug. Some authors hypothesize that the activation of the mesocorticolimbic reward system triggers an attention allocation to alcohol-associated cues. Yet, no functional magnetic resonance imaging (fMRI) studies examining this proposition are available. In this fMRI study we investigate the association between attentional bias and neural cue reactivity. Thirty-eight recently abstinent alcohol-dependent patients were examined. fMRI was used to study cue reactivity during the presentation of alcohol-related pictures. A modified visual dot-probe task was used to assess attentional bias. Alcohol-dependent patients showed an attentional bias to alcohol-associated cues as well as cue-induced fMRI activation in response to alcohol-related stimuli in limbic and reward-related brain regions and visual areas. We found a positive correlation between cue-induced brain activation and attentional bias score in a network including frontal, temporal and subcortical regions. This study is the first demonstrating that, in line with previous suggestions, cue induced activation of the mesocorticolimbic reward system triggers focusing attention to substance-associated cues. However, this association could also be bidirectional with the attentional bias enhancing cue-induced neural activity.